THE EFFECT OF ATTRACTOR MATERIAL ON PELAGIC FISH CAPTURED USING PAYANG BUGIS IN PASAURAN WATERS, PROVINCE OF BANTEN - Roza Yusfiandayani (Research Center for Fisheries, 2011)
Rumpon (fish aggregating device) as an auxiliary gear operated in Pasauran waters, Sunda Strait was longer and more widely used in Indonesia to catch pelagic fish. The characteristic speciescomposition, size, and gonado somato index (GSI) pelagic fish around 3 kinds of rumpon attractor materials, i.e. Cocos nucifera, Nypa fructican, and Areca catechu leaves will determine the effects of attractor materials will affect the sustainability of pelagic fish associated. Identification and composition length, weight and gonado somato index pelagic fish were identified in this research with different attractor material in all seasons. Experimental fishing carried out by using payang Bugis. The result show that the Cocos nucifera leaves are the best attractor material based on the number of fish species and durability in all seasons. Further, the gonado somato index of small pelagic fish were caught around rumpon are gonado somato index I 4%, gonado somato index II 33%, gonado somato index III 35%, gonado somato index IV 25%, and gonado somato index V 3%. Pelagic fish around attractor materials have gonado somato index I-III 72%. This result indicated that the small pelagic fish caught around rumpon are immature fish.